Vitamin D insufficiency and its association with adipokines and atherogenic indices in patients with metabolic syndrome: A case-control study - Amirkhizi, Farshad; Khademi, Zeinab; Hamedi−Shahraki, Soudabeh; Rahimlou, Mehran (Frontiers in Endocrinology, 2023)
Vitamin D deficiency is one of the most common nutritional disorders in most countries of the world. The present study was designed and implemented with the aim of investigating the relationship between vitamin D deficiency and the level of adipokines, atherogenesis indicators and factors related to metabolic syndrome. This case-control study was done on 195 patients with metabolic syndrome aged 20-50 y who attended the health centers in Zabol County, northeast Iran, between April 2021 and January 2022. Anthropometric and biochemical parameters were measured for all subjects with standard methods. To determine serum 25(OH)D levels, we used enzymatic linked immunosorbent assay (ELISA) kits. Atherogenic index of plasma (AIP) was calculated as log (TG/HDL-c). The visceral adiposity index (VAI) and the lipid accumulation product (LAP) were estimated according to standard formulas. Participants in the case group had lower serum levels of 25(OH)D compared to controls (19.8 ± 6.2 ng/ml vs. 41.2 ± 9.7ng/ml, P<0.001). We found that the mean serum levels of fasting blood sugar (P=0.023) and TG (P=0.008) as well as HOMA-IR (P=0.023) were significantly higher in the cases compared to controls. Also, patients with MetS and vitamin D insufficiency (cases) had higher AIP (P=0.040) and LAP (P=0.012) than controls. Furthermore, serum 25(OH)D levels showed significant inverse correlations with serum RBP-4 and a positive correlation with serum omentin-1 concentrations. The results of the present study showed that vitamin D deficiency correlated with some of the cardiometabolic risk factors among the patients with MetS.